Meningkatkan Percaya Diri Siswa melalui Teknik Cognitive Defusion - Saputra, Wahyu Nanda Eka; Prasetiawan, Hardi (Jurnal Kajian Bimbingan dan Konseling, 2018)
This study aims to identify the effectiveness of cognitive defusion technique to increase students’ self confidence. This study used a pre-experimental design with one group pre-test post-test design. Subject in this study were six vocational high school student which have low self-confidence. The instrument used is self-confidence scale. To analyze the subjects’ self confidence after receiving cognitive defusion technique, we use the wilcoxon sign test. The results confirm that students' confidence level score were increase after being treat using cognitive defusion technique. It can be concluded that cognitive defusion technique are effective for improving students' self-confidence.